2017
DOI: 10.1159/000480224
|View full text |Cite
|
Sign up to set email alerts
|

Higher versus Lower Continuous Renal Replacement Therapy Intensity in Critically ill Patients with Liver Dysfunction

Abstract: Aims: To study the association between higher versus lower continuous renal replacement therapy (CRRT) intensity and mortality in critically ill patients with combined acute kidney injury and liver dysfunction. Methods: Post-hoc analysis of patients with liver dysfunction (Sequential Organ Failure Assessment liver score ≥2 or diagnosis of liver failure/transplant) included in the Randomized Evaluation of Normal versus Augmented Level renal replacement therapy (RENAL) trial. Results: Of 444 patients, 210 (47.3%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 22 publications
(27 reference statements)
2
3
0
Order By: Relevance
“…Similar to published data on CRRT in the context of the critically ill, 15,[17][18][19] in our study, patients who underwent CRRT had significantly higher mortality. These patients were sicker, as we offered CRRT to only hemodynamically unstable patients.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Similar to published data on CRRT in the context of the critically ill, 15,[17][18][19] in our study, patients who underwent CRRT had significantly higher mortality. These patients were sicker, as we offered CRRT to only hemodynamically unstable patients.…”
Section: Discussionsupporting
confidence: 91%
“…In our study, a cut‐off MELD above 35 and serum bilirubin more than 23 mg/dL and patients with AARC grade 3 were associated with higher dialysis requirements in the competing risk analysis. Similar to published data on CRRT in the context of the critically ill, 15,17–19 in our study, patients who underwent CRRT had significantly higher mortality. These patients were sicker, as we offered CRRT to only hemodynamically unstable patients.…”
Section: Discussionsupporting
confidence: 90%
“…[64][65][66] Several studies have recommended initiating dialysis when the serum ammonia level is three times the upper limit of normal or if the patient displays signs of severe HE. [66][67][68] Due to similar clearance properties of ammonia to urea, continuous venovenous hemofiltration (CVVH) or intermittent hemodialysis (IHD) can be considered. CVVH is recommended over IHD due to lower fluctuations in intracranial pressure (ICP) and improved hemodynamic stability in the setting of acute kidney injury (AKI).…”
Section: Management Of Acute Liver Failure Diagnosis and Management Omentioning
confidence: 99%
“…64,67,113,114 This functional impairment is due to a complex interplay between extrarenal vasodilation and renal arteriolar vasoconstriction coupled with inadequate cardiac output. 68 Early initiation of RRT has been favored by many liver transplant centers. Studies comparing continuous renal replacement therapy (CRRT) versus IHD have noted greater variations in hemodynamic parameters and ICPs with IHD.…”
Section: Coagulopathy In Acute Liver Failurementioning
confidence: 99%
“…90 Trials comparing convective flow rates of 40 ml/kg/h have not shown improved patient survival compared to those treated with 25 ml/kg/h. 91…”
Section: Introductionmentioning
confidence: 99%